Midiatização e circulação nos processos de call centers: perspectivas comunicacionais para o estudo da produção e recepção no universo do telemarketing - Chu, Daniel Burin (Universidade do Vale do Rio dos Sinos, 2015)
The paper presents an analysis of the environment that sets the telemarketing in Brazilian society. For this a thorough observation of a Customer Service ( Call Center ) was held in Porto Alegre. Tried to verify the communication logic, and the main work done by telemarketers. The dissertation tries to verify both sides of the case: producers (telemarketing operators) and receivers (telemarketing consumers). In circulation environment, and Mediazation, offer the reader a search, a method, and the present situation of the matter Call Center-Telemarketing, in the media world. This was done mainly by the analysis of site “Here Claim” ( reclameaqui.com.br ), and the Youtube Channel, “The Funds Door”. We conducted 11 interviews with producers, and 11 interviews with recipients. For this we used the “clinical method” of Piaget , via Delval (2002 ), to know the thoughts of those involved in the processes. We propose a triadic model of analysis, from the observation of Call Centers universe. This triad is formed by the following categories: “strangeness”; “incommunicado” ; “ancestry”. This is the engine of research, and it is for this triad walks throughout our dissertation. The working method is preferably marked by abductive inferences, and it should be noted that the three categories listed, are part of a highly hypothetical and inferential process, trying to give appropriate answers to the phenomenon.
Keywords: Circulação; Midiatização; Telemarketing; Método clínico; Call center; Circulation; Mediazation; Clinical method; ACCNPQ::Ciências Sociais Aplicadas::Comunicação